Impacts of Organizational Culture on Leadership’s Decision-Making - Jalal, Akram (Journal of Advances in Management Sciences & Information Systems, 2017)
Variances in cultural performances cause disagreement between team members. The aim of this paper is to explore the influences of organisational multi-culture on leadership decision-making process. Hypotheses were proposed to develop an appropriate conceptual research model. The data collection was accomplished using an online structured questionnaire survey with global respondents. 50 questionnaires were distributed and only 39 valid responds were returned. Correlation and regression statistical analysis was applied to measure the relationships between independent variables: cultural diversity, communication, teamwork, learning and development, trust, obligation and cohesion, productive team work with dependent variable: leadership’s decision-making. The findings show that leadership’s decision-making process was significantly influenced by organisational cultural diversity.